Equilibrium kinetics of self-assembling, semi-flexible polymers. (12th July 2018) - Fan Lee, Chiu
Abstract: Self-assembling, semi-flexible polymers are ubiquitous in biology and technology. However, conflicting accounts of the equilibrium kinetics remain for such an important system. Here, by focusing on a dynamical description of a minimal model in an overdamped environment, I identify the correct kinetic scheme that describes the system at equilibrium in the limits of high bonding energy and dilute concentration.